2019
DOI: 10.1016/j.radonc.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The normal tissue complication probability model-based approach considering uncertainties for the selective use of radiation modality in primary liver cancer patients

Abstract: To predict the probability of radiation-induced liver toxicity (RILT) and implement the normal tissue complication probability (NTCP) model-based approach considering confidence intervals (CIs) to select patients for new treatment techniques, such as proton beam therapy, based on a certain NTCP reduction (DNTCP) threshold for primary liver cancer patients. Methods and materials: Common Toxicity Criteria for Adverse Events (CTCAE) grade !2 RILT was scored. The Lyman NTCP models predicting the probability of CTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…The absence of validated multivariate models applicable for HL patients prevented to implement the selection strategies suggested by Langendijk and realized by Rwigema or Cheng [9][10][11]13] for head and neck or Prayongrat [14] for liver. This is a clear need and intensive investigations shall be performed in the near future in this area to provide reliable model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of validated multivariate models applicable for HL patients prevented to implement the selection strategies suggested by Langendijk and realized by Rwigema or Cheng [9][10][11]13] for head and neck or Prayongrat [14] for liver. This is a clear need and intensive investigations shall be performed in the near future in this area to provide reliable model.…”
Section: Discussionmentioning
confidence: 99%
“…It is absolutely obvious that, given the small sample size of the study, the approach suggested here cannot be considered more than a feasibility aiming to pave the path for more appropriate and comprehensive models in view of any clinical applicability [9][10][11][12][13][14][15]. Fig.…”
Section: Model Based Selection Of the Appropriate Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there have been normal tissue complication probability (NTCP) models for predicting risk of RILD based on dose–volume statistics and mathematical models, among which the most common is the Lyman–Kutcher–Burman (LKB) model [ 3–7 ]. A number of clinical risk factors other than the dosimetric profile were reported for RILD, including male gender, Child–Pugh (CP) classification, viral hepatitis infection, presence of portal vein thrombosis (PVT), and prior and concurrent treatments [ 3 , 5 , 7–9 ]. It was also reported that worsening of liver function not related to irradiation is often difficult to be distinguished from RILD; confounding factors, such as other locoregional treatments, worsening of cirrhosis itself or other hepatotoxic effects, may also be related to the hepatic toxicities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty in dose delivery and model parameters were associated with model uncertainty, which significantly affected the accuracy of a model-based approach [ 24 ]. There has been a previous study assessing the uncertainty or the confidence interval (CI) for the LKB model [ 7 ], but not for a multivariable NTCP model for RILD. Underestimation of NTCP and ∆NTCP can lead to the loss of the opportunity to benefit from PBT, whereas overly cautious practice might cause unnecessary use of this high-cost treatment.…”
Section: Introductionmentioning
confidence: 99%